Tajikistan Country Gender Assessment - World Bank (World Bank, Washington, DC, 2021)
Tajikistan has a lot to show in terms of creating an enabling policy framework for gender equity, yet large gendered challenges remain. The global COVID-19 outbreak is impacting economies around the world, including Tajikistan, in an unprecedented manner and aggravates existing gender challenges. This report is presenting achievements made and challenges still to be addressed in view of gender-equity in Tajikistan, based on a desk study covering using most recent material from Tajikistan national sources, the World Bank, development partners and others. It is oriented towards key strategic objectives of the World Bank Group (WBG) Gender Strategy for the period of FY17-FY23 with relevance for the Tajikistan context.